The identification and treatment of common skin infections - Anderson, B. J.; Wilz, L.; Peterson, A. (Journal of Athletic Training, 2023)
Skin conditions are a common problem addressed by medical providers. Up to 25% of individuals in the United States will seek attention for these conditions each year. The same problem occurs in the athletic training room, where athletes with infectious skin conditions can be seen. Most conditions are simple and can be treated without concern for spread to susceptible athletes. However, others can be quite serious and spread rapidly through a team and opponents during competition. Knowledge of the different types of skin infections is necessary to help treat these athletes and prevent spread to others. With proper diagnosis and treatment, certified athletic trainers can keep the athlete off the field of play for a minimum period and prevent transmission.